Front Cover: Chemo‐ and Enantioselective Photoenzymatic Ketone Reductions Using a Promiscuous Flavin‐dependent Nitroreductase (ChemCatChem 8/2022). Issue 8 (21st April 2022) - Prats Luján, Alejandro; Bhat, Mohammad Faizan; Saravanan, Thangavelu; Poelarends, Gerrit J.
Abstract : The Front Cover shows the usefulness of the photocatalyst Ru(bpy)3 Cl2 under irradiation with blue light for expanding the catalytic repertoire of a flavin‐dependent nitroreductase, using glucose dehydrogenase (GDH) for regeneration of the essential NADH cofactor. In their Research Article, A. Prats Luján, M. F. Bhat et al. report the discovery of a flavoenzyme, BaNTR1, that is able to promote enantio‐ and chemoselective photoenzymatic reductions of a broad range of ketones to yield the corresponding alcohols with high conversions and outstanding enantiopurity. Most importantly, BaNTR1 was able to promote the photoenzymatic reduction of various α, ß‐unsaturated ketones to give the corresponding optically pure alcohols without reducing the C=C or C≡C bond, demonstrating its astoundingly high chemoselectivity. More information can be found in the Research Article by A. Prats Luján, M. F. Bhat et al.